Mental Health, Well-Being, and Psychological Flexibility in the Stressful Times of the COVID-19 Pandemic - Wąsowicz, Grażyna; Mizak, Szymon; Krawiec, Jakub; Białaszek, Wojciech (Frontiers in Psychology, 2021)
This study investigated the relationships between selected emotional aspects of mental ill-health (depression, anxiety, and stress, DASS) and mental well-health (well-being) experienced during the COVID-19 pandemic. The theoretical model of the study was based on Martin Seligman’s positive psychology and PERMA theory and Paul Wong’s Existential Positive Psychology 2.0 Theory, which postulates that negative experiences contribute to well-being and personal growth. The static approach was complemented by exploring the mediating role of psychological flexibility (defined as acceptance and action in the current situation) in the relationship between negative emotions and well-being. The data were collected during the initial phase of the COVID-19 pandemic from 277 participants (221 women), aged M = 33.83, SD = 12.77. The results confirmed that negative emotions correlated negatively with various domains of well-being (PERM), except for accomplishment (completing tasks and fulfill daily responsibilities). Moreover, negative emotions were related to the general well-being through psychological flexibility in that higher depression, anxiety, and stress were associated with lower psychological flexibility, which decreased general well-being. Moreover, negative emotions were shown to be beneficial, having an adaptive effect that allows individuals to maintain their ability to cope with the situation, reach goals, and fulfill daily duties and responsibilities despite critical, stressful situation (like the COVID-19 pandemic) that limit their psychological flexibility. This observation confirmed the positive potential of negative aspects of life postulated within Existential Positive Psychology.